Understanding Cancer Worry Among Patients in a Community Clinic-Based Colorectal Cancer Screening Intervention Study. Issue 4 (July 2018) - Christy, Shannon M.; Schmidt, Alyssa; Wang, Hsiao-Lan; Sutton, Steven K.; Davis, Stacy N.; Chavarria, Enmanuel; Abdulla, Rania; Quinn, Gwendolyn P.; Vadaparampil, Susan T.; Schultz, Ida; Roetzheim, Richard; Shibata, David; et al.
Abstract : Background: To reduce colorectal cancer (CRC) screening disparities, it is important to understand correlates of different types of cancer worry among ethnically diverse individuals. Objectives: The current study examined the prevalence of three types of cancer worry (i.e., general cancer worry, CRC-specific worry, and worry about CRC test results) as well as sociodemographic and health-related predictors for each type of cancer worry. Methods: Participants were aged 50–75, at average CRC risk, nonadherent to CRC screening guidelines, and enrolled in a randomized controlled trial to increase CRC screening. Participants completed a baseline questionnaire assessing sociodemographics, health beliefs, healthcare experiences, and three cancer worry measures. Associations between study variables were examined with separate univariate and multivariable logistic regression models. Results: Responses from a total of 416 participants were used. Of these, 47% reported experiencing moderate-to-high levels of general cancer worry. Predictors of general cancer worry were salience and coherence (a OR = 1.1, 95% CI [1.0, 1.3]), perceived susceptibility (a OR = 1.2, 95% CI [1.1, 1.3), and social influence (a OR = 1.1, 95% CI [1.0, 0.1]). Fewer (23%) reported moderate-to-high levels of CRC-specific worry or CRC test worry (35%). Predictors of CRC worry were perceived susceptibility (a OR = 1.4, 95% CI [1.3, 1.6]) and social influence (a OR = 1.1, 95% CI [1.0, 1.2]); predictors of CRC test result worry were perceived susceptibility (a OR = 1.2, 95% CI [1.1, 1.3) and marital status (a OR = 2.0, 95% CI [1.1, 3.7] for married/partnered vs. single and a OR = 2.3, 95% CI [1.3, 4.1] for divorced/widowed vs. single). Discussion: Perceived susceptibility consistently predicted the three types of cancer worry, whereas other predictors varied between cancer worry types and in magnitude of association. The three types of cancer worry were generally predicted by health beliefs, suggesting potential malleability. Future research should include multiple measures of cancer worry and clear definitions of how cancer worry is measured.